The Level of Consumer Knowledge of Doen's Antacid Self-Medication at Narisa Pharmacy - Herman Herman; Achmad Amiruddin; A. Sri Reski Ananda (Jurnal Farmasi Sandi Karsa, 2023)
Gastritis is a disease that is generally suffered by the community due to several factors, for example, irregular eating patterns, lifestyle and one of them is the increasing activity of the community so that they do not have time to regulate their diet. This makes Swamedication 3 an alternative that is often taken by the community to deal with gastritis complaints, but the lack of basic knowledge about correct Gastritis self-medication often results in medication errors (Medication errors). This study aims to determine the level of consumer knowledge about doen antacid self-medication at the Narisa Pharmacy which will be carried out in March 2023 at the Narisa Pharmacy, Makassar City. This type of research uses descriptive methods, namely research that includes surveys with data collection in the form of questionnaires with a total of 52 respondents. The sampling technique uses a nonprobability sampling technique, namely saturated sampling. the results of this study indicate that the percentage of respondents' answers is 92.69%. Based on these results it can be concluded that the level of consumer knowledge about doen antacid self-medication at the Narisa Pharmacy is included in the good category.